2008
DOI: 10.1186/1746-4811-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence imaging accurately quantifies freezing damage and cold acclimation responses in Arabidopsis leaves

Abstract: Background: Freezing tolerance is an important factor in the geographical distribution of plants and strongly influences crop yield. Many plants increase their freezing tolerance during exposure to low, nonfreezing temperatures in a process termed cold acclimation. There is considerable natural variation in the cold acclimation capacity of Arabidopsis that has been used to study the molecular basis of this trait. Accurate methods for the quantitation of freezing damage in leaves that include spatial informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 34 publications
8
96
0
3
Order By: Relevance
“…Furthermore, the exogenous application of maltose led to a reduced increase in conductivity in cold-sensitive plants such as OsMYB30-OE plants and some coldsensitive rice accessions, suggesting that maltose could reduce the damage to the cell membrane. Besides this, the chlorophyll fluorescence F v /F m ratio, which has been adopted as another physiological indicator reflecting the photosynthetic electron transport chain during cold stress treatment (Rosinski and Atchley, 1998;Baker and Rosenqvist, 2004;Ehlert and Hincha, 2008;Mishra et al, 2014;Thalhammer et al, 2014), was decreased in the rice plants with lower maltose accumulation (Fig. 4, E and F).…”
Section: Complexity Of Osmyb30 Regulation In Starch and Sugar Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the exogenous application of maltose led to a reduced increase in conductivity in cold-sensitive plants such as OsMYB30-OE plants and some coldsensitive rice accessions, suggesting that maltose could reduce the damage to the cell membrane. Besides this, the chlorophyll fluorescence F v /F m ratio, which has been adopted as another physiological indicator reflecting the photosynthetic electron transport chain during cold stress treatment (Rosinski and Atchley, 1998;Baker and Rosenqvist, 2004;Ehlert and Hincha, 2008;Mishra et al, 2014;Thalhammer et al, 2014), was decreased in the rice plants with lower maltose accumulation (Fig. 4, E and F).…”
Section: Complexity Of Osmyb30 Regulation In Starch and Sugar Metabolismmentioning
confidence: 99%
“…According to previous studies, the increase in the maltose content could help in the protection of the photosynthetic electron transport chain Guy, 2004, 2005), in which the chlorophyll fluorescence F v /F m ratio has been used as an indicator to quantify cold tolerance in Arabidopsis, rice, and other plants (Baker and Rosenqvist, 2004;Ehlert and Hincha, 2008;Mishra et al, 2014;Thalhammer et al, 2014). We measured the F v /F m ratio after cold stress treatment, and the results showed that the F v /F m ratio was decreased significantly in the three OsMYB30-OE plants compared with ZH11 (Fig.…”
Section: Maltose May Contribute To Cell Membrane Protection During Comentioning
confidence: 99%
“…The effect of altered COR15 protein levels on Arabidopsis freezing tolerance was tested using two independent approaches: an electrolyte leakage assay to assess freezing damage to the plasma membrane and the tonoplast (Rohde et al, 2004), and a chlorophyll fluorescence imaging assay to obtain information on the inactivation of photosynthesis and the intactness of chloroplast membranes (Ehlert and Hincha, 2008). As shown in Figure 2, freezing tolerance is expressed as the temperature at which 50% damage occurred or LT 50 .…”
Section: Cor15a and Cor15b Are Necessary For Arabidopsis To Attain Fumentioning
confidence: 99%
“…Chlorophyll fluorescence imaging analysis was performed on dark adapted leaves directly after thawing (i.e. omitting the incubation in distilled water), with freezing and thawing conditions identical to those described above, integrating measurements over the whole leaf area (Ehlert and Hincha, 2008). The LT 50 was calculated as the logEC 50 value derived from sigmoidal curves using GraphPad Prism3 software (Rohde et al, 2004).…”
Section: Determination Of Leaf Freezing Tolerancementioning
confidence: 99%
“…The moderate correlation obtained between clonal electrolytic leakage and photosystem efficiency following artificial freezing was not surprising, as the two methods take into account different parameters and while electrolyte leakage can be considered an estimate of the cellular membrane damage, F v /F m shows the efficiency of photosystem II, which can be impaired even without physical membrane damage (Saibo et al 2009;Yamamoto et al 2008). The two techniques were used to measure cold damage at different freezing temperatures in Arabidopsis (Ehlert and Hincha 2008) and while a general correspondence was found, differences between the two methods were highlighted. According to the results presented in this paper, most of rank changing was observed for those accessions showing average cold tolerance.…”
Section: Discussionmentioning
confidence: 99%